2023
DOI: 10.2147/dmso.s390999
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Characteristics of Gestational Diabetes Mellitus and the Effects on Pregnancy Outcomes

Abstract: Objective To describe the metabolic characteristics of gestational diabetes mellitus (GDM) and assess their effects on perinatal outcomes. Methods A two-center nested case‒control study was designed, including 192 pregnant women with GDM and 191 pregnant women with normal glucose tolerance (NGT). Serum glucose and insulin concentrations based upon the 75 g oral glucose tolerance test (OGTT) were measured. Several indices were calculated to describe the metabolic charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…A study by Luo et al [ 8 ] in a recent issue reported that individualised nutrition interventions, including calorie restriction, adoption of smaller and more frequent meals, and guidance on exercise, were effective at lowering pregnant weight gain, fasting plasma glucose, haemoglobin A1c and the incidence of neonatal adverse events, such as premature birth, macrosomia and respiratory distress syndrome, in Chinese women with GDM. However, Luo et al [ 9 ] did not specifically document how adequately post-prandial glycaemia was controlled by the nutritional intervention. The latter is of major importance, as the majority of Han Chinese women with GDM exhibit elevated plasma glucose at the 1 and 2-h time points of an oral glucose tolerance test, with normal or modestly high fasting glucose.…”
Section: Postprandial Hyperglycaemia In Gdm: More Attention Is Neededmentioning
confidence: 99%
“…A study by Luo et al [ 8 ] in a recent issue reported that individualised nutrition interventions, including calorie restriction, adoption of smaller and more frequent meals, and guidance on exercise, were effective at lowering pregnant weight gain, fasting plasma glucose, haemoglobin A1c and the incidence of neonatal adverse events, such as premature birth, macrosomia and respiratory distress syndrome, in Chinese women with GDM. However, Luo et al [ 9 ] did not specifically document how adequately post-prandial glycaemia was controlled by the nutritional intervention. The latter is of major importance, as the majority of Han Chinese women with GDM exhibit elevated plasma glucose at the 1 and 2-h time points of an oral glucose tolerance test, with normal or modestly high fasting glucose.…”
Section: Postprandial Hyperglycaemia In Gdm: More Attention Is Neededmentioning
confidence: 99%
“…It can evolve into type 2 diabetes mellitus (T2DM) in the mother after pregnancy, especially when maternal obesity is present, although it usually disappears after childbirth [1]. In most pregnancies in which it occurs, it appears to be caused by a pancreatic response due to an inability to compensate for insulin resistance in the gestational stage [3].…”
Section: Introductionmentioning
confidence: 99%